2005
DOI: 10.3168/jds.s0022-0302(05)72906-4
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Bovine Milk Fat Globule Membrane as a Potential Nutraceutical

Abstract: For the last 15 yr, a great deal of knowledge has been accumulated on health beneficial factors, protein and nonprotein, of bovine milk fat globule membrane (MFGM). Among the health-beneficial components of the MFGM are cholesterolemia-lowering factor, inhibitors of cancer cell growth, vitamin binders, inhibitor of Helicobacter pylori, inhibitor of beta-glucuronidase of the intestinal Escherichia coli, xanthine oxidase as a bactericidal agent, butyrophilin as a possible suppressor of multiple sclerosis, and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
308
0
19

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(329 citation statements)
references
References 54 publications
2
308
0
19
Order By: Relevance
“…Many studies have shown that the MFG size and MFGM features (structure and composition) can influence milk fat functionalities such as its technological properties (butter yields, index of firmness, fat content of the cheese…), sensory qualities (texture, flavor, moisture, color) and nutritional quality (lipid, FA and protein compositions) (Goudédranche et al, 2000;O'Mahomy et al, 2005;Spitsberg, 2005;Lopez, 2011;Logan et al, 2015). On the other hand, some studies suggest that producing milk naturally modified in terms of MFG size could be possible using factors at the farm scale.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the MFG size and MFGM features (structure and composition) can influence milk fat functionalities such as its technological properties (butter yields, index of firmness, fat content of the cheese…), sensory qualities (texture, flavor, moisture, color) and nutritional quality (lipid, FA and protein compositions) (Goudédranche et al, 2000;O'Mahomy et al, 2005;Spitsberg, 2005;Lopez, 2011;Logan et al, 2015). On the other hand, some studies suggest that producing milk naturally modified in terms of MFG size could be possible using factors at the farm scale.…”
Section: Introductionmentioning
confidence: 99%
“…The phospholipid content of buttermilk can reach up to seven times that of whole milk [25]. Mainly composed of phosphatidylethanolamine (PE), phosphatidylcholine (PC), sphingomyelin (SM), phosphatidylinositol (PI), phosphatidylserine (PS), glucosylceramide (GluCer) and lactosylceramide (LacCer), MFGM phospholipids have been associated recently with numerous health benefits such as protective effects against cancer, stress, Alzheimer's disease and gastrointestinal pathogens as well as hypercholesterolaemia as reviewed in [4,24,26]. For example, SM, which represents approximately 25% of the MFGM phospholipids, has been shown to reduce intestinal absorption of cholesterol in rats [6,12,21].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of MFGM proteins has been surveyed and examined by researchers, especially their bioactivities [17,18]. Because of the functional and nutritional features of MFGM proteins, many components in mammalian milk have been examined [19,20]. The different bioactive compounds on the MFGM are still being researched, but there are a variety of beneficial compounds such as lactoferrin, IgG, secretary IgA, sialic acid, phospholipids, and gangliosides.…”
Section: Introductionmentioning
confidence: 99%